URGENSI INDONESIA MENJADI NEGARA PIHAK STATUTA ROMA BAGI PERLINDUNGAN HAM DI INDONESIA - Marfuatul Latifah (Sekretariat Jenderal DPR RI, 2014)
Rome Statute as an international agreement has the jurisdiction on the enforcement of the prosecutions of grave human rights violations. Although Indonesia attended the conference which endorsed the Rome Statute in 1998, in fact, the country has not yet ratified it. Indonesia worries that the Rome Statute gives chance to punish Indonesians in cases of past serious human rights violations. This study’s finding, against, however, that worrisome due to the existence of the principle of the non-retroactivity and the complementary of the international criminal court. The implementation of the International Criminal Court will actually respect national law, especially which will make more effective the protection of human rights. As a Party State, Indonesia will obtain a lot of benefits in absorbing the provisions in the Rome Statute into national law.